High-quality-draft genome sequence of the fermenting bacterium Anaerobium acetethylicum type strain GluBS11T (DSM 29698). Issue 1 (December 2017) - Patil, Yogita; Müller, Nicolai; Schink, Bernhard; Whitman, William; Huntemann, Marcel; Clum, Alicia; Pillay, Manoj; Palaniappan, Krishnaveni; Varghese, Neha; Mikhailova, Natalia; Stamatis, Dimitrios; Reddy, T.; et al.
Abstract Anaerobium acetethylicum strain GluBS11T belongs to the familyLachnospiraceae within the orderClostridiales . It is a Gram-positive, non-motile and strictly anaerobic bacterium isolated from biogas slurry that was originally enriched with gluconate as carbon source (Patil, et al., Int J Syst Evol Microbiol 65:3289-3296, 2015). Here we describe the draft genome sequence of strain GluBS11T and provide a detailed insight into its physiological and metabolic features. The draft genome sequence generated 4, 609, 043 bp, distributed among 105 scaffolds assembled using the SPAdes genome assembler method. It comprises in total 4, 132 genes, of which 4, 008 were predicted to be protein coding genes, 124 RNA genes and 867 pseudogenes. The G + C content was 43.51 mol %. The annotated genome of strain GluBS11T contains putative genes coding for the pentose phosphate pathway, the Embden-Meyerhoff-Parnas pathway, the Entner-Doudoroff pathway and the tricarboxylic acid cycle. The genome revealed the presence of most of the necessary genes required for the fermentation of glucose and gluconate to acetate, ethanol, and hydrogen gas. However, a candidate gene for production of formate was not identified.